2021
DOI: 10.7251/agren2103067s
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Lathyrus sativus L. collection and characteristics of seeds produced in Slovenia and Serbia

Abstract: Grass pea (Lathyrus sativus L.) is a less common and nearly forgotten crop in many countries, including Slovenia and Serbia. In the present study, genetic analysis and seed characteristics of the collection of 21 grass pea accessions from Southeast Europe were examined. The collection was produced in an open-field experiment in two countries/ locations, i.e. Slovenia/Ljubljana – Jablje and Serbia/ Novi Sad – Rimski Šančevi, during the 2019 growing season. To analyse genetic diversity, specific high polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The TI activity showed higher variability at the site in Slovenia (CV = 27.1%, Table 2), where 25 grass pea accessions were tested, compared to 12 grass pea accessions tested in Serbia (CV = 12.9%, Table 3). Sinkovič et al (2021) previously reported high genetic diversity and differences in seed traits in grass pea accessions from south-eastern Europe.…”
Section: Resultsmentioning
confidence: 96%
“…The TI activity showed higher variability at the site in Slovenia (CV = 27.1%, Table 2), where 25 grass pea accessions were tested, compared to 12 grass pea accessions tested in Serbia (CV = 12.9%, Table 3). Sinkovič et al (2021) previously reported high genetic diversity and differences in seed traits in grass pea accessions from south-eastern Europe.…”
Section: Resultsmentioning
confidence: 96%